(untitled) (Nexus International Journal of Science and Education, 2024)
The study uncovered elementary teachers' lifestyles and financial management practices and how these affect their teaching. It employed a phenomenological research design to determine the experiences and perceptions of the eight (8) participants. The eight (8) Babak District, Division of Island Garden City of Samal (IGACOS) teachers were the participants. The researcher utilized the purposive sampling design since the participants were chosen based on the criteria or purpose of the study. In gathering data, the researcher used an in-depth interview questionnaire. The researcher developed the interview questionnaire, which was answered by the participants orally. The finding revealed that in the lifestyles of teachers based on personal finances, the generated themes were unforeseen costs, concern over salary loans, and financial stress-related difficulties. Meanwhile, the themes for teachers coping with financial management challenges were balancing expenditures, establishing a financial buffer, and attending financial training. Lastly, the emerging themes on education management insights drawn from the experiences were prioritization matters, the importance of financial resilience, and teaching money management to students. The themes suggest that educators play a unique role in society. By imparting knowledge of financial management, they were responsible for securing the nation's and its citizens' families' future. For teachers to do their jobs properly, they must develop solid financial management abilities to become good student models.